Effect Size Analysis of the Influence of Science Teaching Materials Based on Scientific Approach on Students’ Learning Outcomes - Dwita Fitri, Anisa Dwita Fitri; Asrizal, Asrizal; Festiyed, Festiyed (Universitas Negeri Padang, 2023)
This research analyzes the influence of teaching materials in science and physics learning based on a scientific approach on student learning outcomes determined through Effect Size. This research uses a descriptive study method. Research data was obtained from 20 journals regarding the influence of scientific approach-based science and physics teaching materials on student learning outcomes. The study is based on three categories, namely aspects of student learning outcomes, level of education and type of teaching materials. The research results show that in the aspects of student learning outcomes, namely knowledge, attitudes and skills, all three have a high measurement category with an effect size value of 1.05 each; 1.06 and 0.94. The influence of scientific approach-based teaching materials on high school students is better than on middle school students with mean effect sizes of 1.06 (high) and 0.70 (medium) respectively. The use of worksheets with a scientific approach has the greatest influence on student learning outcomes compared to other types of teaching materials with an effect size value of 1.15 (very high).